Computerized Exposure Therapy for Spider Phobia: Effects of Cardiac Timing and Interoceptive Ability on Subjective and Behavioral Outcomes. Issue 1 (January 2019) - Watson, David R.; Garfinkel, Sarah N.; Gould van Praag, Cassandra; Willmott, Daniel; Wong, Katherine; Meeten, Frances; Critchley, Hugo D.
ABSTRACT: Objective: Spider phobia is a common form of anxiety disorder for which exposure therapy is an effective first-line treatment. Motivated by the observed modulation of threat processing by afferent cardiac signals, we tested the hypothesis that interoceptive information concerning cardiovascular arousal can influence the outcomes of computerized exposure therapy for spider phobia. Method: Fifty-three normal healthy participants with high spider phobia scores underwent one of the following three modified computerized exposure protocols, defined by the timing of exposure to brief spider stimuli within the cardiac cycle: systole (during afferent baroreceptor firing); diastole (during baroreceptor-quiescent interbeat interval); random (noncontingent on cardiac cycle). Outcomes were judged on phobic and anxiety measures and physiological data (skin conductance). Individuals were also rated on interoceptive accuracy. Results: MANCOVA analysis showed that timing group affected the outcome measures ( F (10, 80) = 2.405, p = .015) and there was a group interaction with interoception ability ( F (15, 110) = 1.808, p = .045). Subjective symptom reduction was greatest in the systolic group relative to the other two groups (diastolic ( t = 3.115, p tukey = .009); random ( t = 2.438, p tukey = .048)), with greatest reductions in those participants with lower interoceptive accuracy. Behavioral aversion reduced more in cardiac-contingent groups than the noncontingent (random) group (diastolic ( t = 3.295, p tukey = .005); systolic ( t = 2.602, p tukey = .032)). Physiological (skin conductance response) responses remained strongest for spider stimuli presented at cardiac systole. Conclusions: Interoceptive information influences exposure benefit. The reduction in the subjective expression of fear/phobia is facilitated by "bottom-up" afferent signals, whereas improvement in the behavioral expression is further dependent on "top-down" representation of self-related physiology (heart rhythm). Individual interoceptive differences moderate these effects, suggesting means to personalize therapy.